Lifetime difference and CP-violating phase in the B-s(0) system - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2007)
From an analysis of the decay Bs0→J/ψ, we obtain the width difference between the light and heavy mass eigenstates ΔΓ(ΓL- ΓH)=0.17±0.09(stat)±0.02(syst)ps-1 and the CP-violating phase s=-0.79±0.56(stat)-0.01+0.14(syst). Under the hypothesis of no CP violation (0), we obtain 1/Γ̄=τ̄(Bs0)=1.52±0.08(stat) -0.03+0.01(syst)ps and ΔΓ=0.12-0.10+0.08(stat)±0.02(syst)ps- 1. The data sample corresponds to an integrated luminosity of about 1.1fb-1 accumulated with the D0 detector at the Fermilab Tevatron collider. This is the first direct measurement of the CP-violating mixing phase in the Bs0 system. © 2007 The American Physical Society.